EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL TIKTOK SEBAGAI MEDIA EDUKASI PENCEGAHAN KEK DI SMAN 6 CIMAHI - Berlian, Selpia; Mahmudah, Umi; Suparman, Suparman; Rahmat, Mamat (Jurnal Gizi dan Dietetik, 2024)
Chronic Energy Deficiency (CED) is prevalent among Indonesian young women, increasing the risk of stunting. Early education, including the use of TikTok, is recommended to prevent CED due to its popularity and accessibility among teenagers. This research aims to determine the effect of nutritional education regarding the prevention of CED through the social media TikTok on knowledge, attitudes and protein energy intake in young women at SMAN 6 Cimahi. The design of this research is a quasi experiment with a pre test - post test with control group design. Simple random sampling was used with a sample size of 52 people, divided into treatment and control groups for education via TikTok and PowerPoint. Data analysis employed various statistical tests like Shapiro Wilk, Wilcoxon, and T-Tests. The research results show that there is an influence of TikTok social media on knowledge, attitudes, energy and protein intake in young women at SMAN 6 Cimahi. In terms of increasing knowledge and attitudes, TikTok social media is more effective as an educational medium than PowerPoint media (p=0.000), but is not effective for energy intake (p=0.103), and is not effective for protein intake (p=0.169). Further research to determine the effectiveness of TikTok social media on energy and protein intake will need to be accompanied by mentoring methods.